1988
DOI: 10.1093/genetics/118.2.181
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro assay for frameshift mutations: hotspots for deletions of 1 bp by Klenow-fragment polymerase share a consensus DNA sequence.

Abstract: The fidelity of in vitro DNA synthesis catalyzed by the large fragment of DNA polymerase I was examined. The templates, specifically designed to detect shifts to the +1 or to the -1 reading frame, are composites of M13mp8 and bacteriophage T4 rIIB DNA and were designed to assist in the identification of the types of frameshifts that are the specific consequence of DNA polymerization errors. In vitro polymerization by the Klenow fragment produced only deletions, rather than the mixture of duplications and delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…So-called spontaneous frameshift deletions are formed during DNA replication, presumably induced by endogenous or exogenous DNA damage (reviewed in ref 1 ). The frequency of such deletions may be influenced by several factors, including DNA sequence context ( ), the editing function of DNA polymerase ( , ), and imbalances in the dNTP pool ().…”
mentioning
confidence: 99%
“…So-called spontaneous frameshift deletions are formed during DNA replication, presumably induced by endogenous or exogenous DNA damage (reviewed in ref 1 ). The frequency of such deletions may be influenced by several factors, including DNA sequence context ( ), the editing function of DNA polymerase ( , ), and imbalances in the dNTP pool ().…”
mentioning
confidence: 99%
“…This includes 221 different single-base substitutions at 114 different template positions (Kunkel & Alexander, 1986; , single-base frame shifts at 150 positions (Kunkel, 1986), and a variety of larger and/or more complex frame shifts. More recently, several assays have been designed to focus on particular subsets of frame-shift errors (de Boer & Ripley, 1988; Kunkel et al" 1989; Papanicolaou & Ripley, 1989; Bebenek . These assays use M13 DNA substrates that normally yield colorless plaques because they contain frame-shift mutations.…”
mentioning
confidence: 99%
“…This possibility is supported by structural studies with oligonucleotides demonstrating that an extra base can exist in conformations that do not disrupt hydrogen bonding of adjacent base pairs [Patel et al, 1982;Hare et al, 1986;Roy et al, 1987;Woodson & Crothers, 1988;Joshua-Tor et al, 1988;Miller et al, 1988; for review, see Patel et al (1987)]. Extra bases may be stabilized by interactions with amino acids in the DNA polymerase (Kunkel, 1986; de Boer & Ripley, 1988;Miller et al, 1988), perhaps by formation of hydrogen bonds with specific nucleotides (Hendry et al, 1981(Hendry et al, , 1984Lacey & Mullins, 1983), which might exclude them from pairing with the other strand.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the deletion included the primosome assembly signal (pas) site, probably resulting in more durable Pol I replication and mutation in sequences located further from ori [ 15 ]. On the other hand, it has been reported that both Pol I and mismatch repair-defective cells may lead to large indels, which probably results in this large fragment deletion [ 48 , 49 ]. In addition, the deletion mutation contains the gene encoding the Rop protein.…”
Section: Discussionmentioning
confidence: 99%